Investigation of Wind Energy Potential in Asia-Pacific Region: Thailand, South Korea and Bangladesh Perspectives - Dahirul Islam, Khandaker (Prince of Songkla University, 2023)
Thesis (Ph.D. (Sustainable Energy Management))--Prince of Songkla University, 2021